Follicular miniaturization in female pattern hair loss: clinicopathological correlations - Messenger, A.G.; Sinclair, R. (British journal of dermatology (1951), 2006)
Summary Background  The pathology of female pattern hair loss (FPHL) is characterized by an increase in the proportion of vellus follicles, manifest as a low terminal/vellus ratio. This is conventionally thought to be due to a progressive miniaturization of terminal hair follicles. There is also a prolongation of the latent period of the hair cycle (kenogen) in both male pattern hair loss and FPHL and follicles in kenogen may be difficult to classify histologically. Therefore, a low terminal/vellus ratio could be due to a preferential increase in the number of terminal follicles in kenogen rather than to a true increase in the number of vellus follicles. Objectives  To establish whether there is an increase in the absolute number of vellus follicles during the progression of FPHL, indicating a process of follicular miniaturization. Methods  We studied 42 women complaining of hair loss. The severity of the hair loss was graded clinically on a five‐point scale from 1 (no obvious hair loss) to 5 (severe hair loss). Three 4‐mm punch biopsies were taken from the frontal scalp of each patient, sectioned horizontally and stained with haematoxylin and eosin. Two levels were studied on each biopsy: through the mid‐infundibular region and through the mid‐isthmus. The following were counted: total follicles, terminal follicles, vellus follicles, anagen and telogen/catagen follicles. The results from the three biopsies from each subject were averaged and statistical evaluations performed on the mean values. Results  There was a progressive decline in mean total follicle count with increasing grade of hair loss (grade 1, 317 cm−2; grade 5, 243 cm−2) and a more pronounced reduction in terminal follicle counts (grade 1, 263 cm−2; grade 5, 96 cm−2). The absolute number of vellus follicles increased from 33 cm−2 (grade 1) to 71 cm−2 (grade 4), declining to 51 cm−2 at grade 5. The terminal/vellus ratio fell from 12·8 (grade 1) to 2·3 (grade 4) and remained at this level thereafter. The proportion of follicles in telogen increased from 13·7% (grade 1) to 31·4% (grade 5). Conclusions  Our results show that there is an increase in vellus follicle numbers with increasing severity of hair loss in women with FPHL, suggesting that terminal follicles do indeed miniaturize. It is possible that there is also an increase in the number of follicles in a latent stage of telogen but this was difficult to assess from our data. The fall in total follicle counts with stabilizing of the terminal/vellus ratio in severe hair loss suggests that miniaturization does not stop with a vellus follicle but progresses to follicular deletion.